2009
DOI: 10.1177/1545968309353608
|View full text |Cite
|
Sign up to set email alerts
|

Hemiparetic Stepping to the Beat: Asymmetric Response to Metronome Phase Shift During Treadmill Gait

Abstract: Although phase correction of gait is slowed when the phase shift is delivered to the nonparetic side compared with the paretic side, phase correction is still present. This may underlie the utility of rhythmic auditory cueing in hemiparetic gait rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 21 publications
5
60
0
1
Order By: Relevance
“…The mean number of targets missed on the paretic and non-paretic sides were similar in our study. Although other studies have shown differences in step adjustments between paretic and non-paretic limbs in response to variable metronome cues [11], our finding is in agreement with studies of visual target stepping paradigms [10] showing equivalent foot-placement control between the ipsilesional and contralesional legs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The mean number of targets missed on the paretic and non-paretic sides were similar in our study. Although other studies have shown differences in step adjustments between paretic and non-paretic limbs in response to variable metronome cues [11], our finding is in agreement with studies of visual target stepping paradigms [10] showing equivalent foot-placement control between the ipsilesional and contralesional legs.…”
Section: Discussionsupporting
confidence: 92%
“…[5,6]), turning (e.g. [7][8][9]) and in initiating and executing step adjustments (particularly to place the foot medially) in response to external cues [10,11]. However, the relationships between poor gait adaptability and functional recovery/mobility are still largely unknown.…”
mentioning
confidence: 99%
“…Audio cues also helped participants with post-stroke gait impairments to show improvements in spatial [22] and temporal symmetry [21]. The step time asymmetry and the paretic (affected leg) step time variability of participants also improved significantly [23], as did the ability to make gait adjustments in response to changes in the cue [24]. Rhythmic cueing is therefore a promising approach, but the use of audio may not be the best medium for in-home or out-and-about scenarios for rehabilitation, where it is important to keep the audio channel clear for reasons of safety, sociability, and to remain aware of the environment.…”
Section: Rhythmic Cueing For Gait Rehabilitationmentioning
confidence: 99%
“…All participants signed an informed consent form after they received information about the purpose and procedure of the experiment, and use of data. The inclusion criteria were [Van Peppen RP et al, 2004] six months or more after stoke onset, [Dickstein R et al, 2004] scores above 24 on the K-MMSE, [Robbins SM et al, 2006] ability to understand verbal instructions, [Mirelman A et al, 2009] ability to walk independently for at least 10 minutes, [Hayden R et al,2009] no orthopedic problems in lower limbs, [Pelton TA et al, 2010] no sensory problems that can affects walking ability. The present study was approved by Sahmyook University Institutional Review Boards and each subject was able to follow instructions and gave informed consent by signing an approved consent form; thus, the rights of human subjects were protected.…”
Section: Subjectsmentioning
confidence: 99%
“…There are various physical therapeutic interventions that are generally used to improve balance and walking ability in stroke patients: task-oriented approach [Van Peppen RP et al, 2004], motor imagery training [Dickstein R et al, 2004], functional electrical stimulation [Robbins SM et al, 2006], robot-assisted training with virtual reality [Mirelman A et al, 2009], rhythmic auditory stimulation [Hayden R et al,2009,Pelton TA et al, 2010, and treadmill training [Hesse S, 2008,Patterson SL et al, 2007.…”
Section: Introductionmentioning
confidence: 99%